The effect of overtraining on serum leptin levels in women national wrestlers - F. Yamaner (H.S. Skovoroda Kharkov National Pedagogical University, 2019)
Purpose: Weight control and weight loss during the periods of wrestling competitions are attached great importance -in order to be successful in wrestling. Leptin hormone level is known to play an important role in the control of body weight. For this reason, the purpose of this study was to investigate the effect of substantial weight loss on serum leptin levels of women wrestlers during competition periods. Material and Methods: Twenty-five women wrestlers who trained for 2015 European Championship from Turkish National Wrestling Team and 26 sedentary women were recruited voluntarily for this study. Serum leptin levels of wrestlers in the experimental group and sedentary women in the control group were measured after overnight fasting before and after 21 days training camp of 2015 European Championship. Results. Statistically significant difference was found in the direction of decrease in body weight, body mass index (BMI), glucose, insulin, cholesterol, triglyceride, LD, VLDL and leptin parameters and increase in HDL parameters before and after training camp in the experimental group ( p < .05 ). There was a statistically significant difference in leptin levels between the control group and women wrestlers ( p < .05 ). There was also a statistically significant difference in leptin levels of wrestlers before and after training camp ( p < .05 ). Conclusion. As a result, the data obtained in the study indicate that intense wrestling trainings in camping period brought about weight loss and decreased leptin levels.